Camp Notes and Other Writings - Yamada, Mitsuye (Book collections on Project MUSE., 1998)
Mitsuye Yamada was born in Kyushu, Japan, and raised in Seattle, Washington, until the outbreak of World War II when her family was removed to a concentration camp in Idaho. Camp Notes and Other Writings recounts this experience. Yamada's poetry yields a terse blend of emotions and imagery. Her twist of words creates a twist of vision that make her poetry come alive. The weight of her cultural experience - the pain of being perceived as an outsider all of her life - permeates her work. Yamada's strength as a poet stems from the fact that she has managed to integrate both individual and collective aspects of her background, giving her poems a double impact. Her strong portrayal of individual and collective life experience stands out as a distinct thread in the fabric of contemporary literature by women. This writers poetry yields a terse blend of emotions & imagery. Her twist of words creates a twist of vision that make her poetry come alive. The weight of her cultural experience-the pain of being perceived as an outsider all of her life-permeates her work. Her strength as a poet stems from the fact that she has managed to integrate both individual & collective aspects of her background, giving her poems a double impact.